Identification of High School Students' Misconceptions on Chemical Bonding With Three Tier Test - Ardiansyah Ardiansyah; Iis Siti Jahro; Ayi Darmana (Universitas Lampung, 2021)
Abstract: Identification of High School Students’ Misconceptions on Chemical Bonding With Three Tier Test. This study aims to determine misconceptions among high school students in Medan city on chemical bonding concepts. The research population was 10th grade senior high school students in Medan City, while the samples were taken from 3 schools (school A, B, and C) in Medan City with cluster random sampling technique, a total of 109 students. Three-Tier Test (TTT) were developed based on indicators that students must master in chemical bonding material. The questions are validated by expert validators so that valid questions are generated. A valid TTT is then given to a sample of students. Furthermore, interviews were conducted with students who experienced misconceptions. All data obtained through the test were processed and analyzed. Results showed students who have misconceptions in high school A, B, and C is 53,33, 41,74, and 54,58 respectively with an average of 48,98%. The misconception occurs largely in ionic bonding(56,58%). In addition, the misconception is also found in the stability elements (51,84%), Lewis symbol and structures (46,18%), and covalent bonding (47,48%)concept. The cause of misconceptions is largely due to the wrong students constructing concepts.Keywords: Misconception, Three-Tier Test, chemical bonding. Abstrak: Identifikasi Miskonsepsi Siswa SMA pada Ikatan Kimia dengan Test Tiga Tingkat. Penelitian ini bertujuan untuk mengetahui miskonsepsi siswa SMA di Kota Medan pada materi ikatan kimia. Populasi penelitian adalah siswa SMA kelas X di kota Medan, sedangkan sampel diambil dari 3 SMA (SMA A, B, dan C) di kota Medan dengan teknik cluster random sampling, sebanyak 109 siswa. Tes Tiga Tingkat (TTT) dikembangkan berdasarkan indikator yang harus dikuasai oleh siswa pada materi ikatan kimia. Soal-soal divalidasi oleh validator ahli sehingga didapatkan soal yang valid. TTT diberikan kepada sampel siswa penelitian. Wawancara dilakukan kepada siswa yang mengalami miskonsepsi. Semua data yang didapatkan, selanjutnya diproses dan dianalisis. Hasil penelitian menunjukkan siswa yang mengalami miskonsepsi di SMA A, B, dan C berturut-turut sebesar 53,33, 41,74, dan 54,58 dengan rerata 48,98%. Miskonsepsi sebagian besar terjadi pada konsep ikatan ion (56,58%). Selain itu, miskonsepsi juga ditemukan pada konsep kestabilan unsur (51,84%), lambang dan struktur lewis (46,18%), dan ikatan kovalen (47,48%). Sebagian besar miskonsepsi disebabkan oleh kesalahan siswa merekonstruksi konsep. Kata kunci: Miskonsepsi, tes tiga tingkat, ikatan kimiaDOI: 10.23960/jppk. v10.i3.2021.17